Components of citrus pulp waste (eureka lemon and clementine) and yellow maize commonly used as livestock feed by south African farmers (Bioagro, 2023)
Citrus is one of the most extensively grown fruits in several parts of the world. Therefore, its inustrial processing produces large amounts of pulp waste. This study was aimed at assessing the nutritive as well as mineral components of citrus pulp waste of Eureka lemon and Clementine from two Citrus farms while drawing potential comparisons with yellow maize for livestock feed. Proximate analyses were done using approved/standard analytical methods of the Association of Official Analytical Chemists (AOAC), while the mineral constituents were analysed using an inductively coupled plasma optical emission spectroscopy (ICP-OES). Proximate evaluation revealed that Eureka lemon and Clementine pulp waste contained comparable amounts of fibre and lipid, and significantly higher protein contents than yellow maize. Meanwhile, minerals including Ca, Mg, K, Na, Zn, Cu, Mn and Fe were significantly higher in the citrus lemon pulp waste than in yellow maize. The study therefore points out that the Citrus pulp waste have the potentials to be put to more relevant livestock nutritional use.
Keywords: Mineral and proximate analysis; nutritional components; Zea mays